Znaczenie norm technicznych i standardów produktów we współczesnej polityce handlowej na przykładzie Japonii - Drelich-Skulska, Bogusława (Significance of Technical Standards of Products in Modern Trade Policies Based on the Example of Japan, 2006)
One of the factors determining globalisation - apart from technical progress and international competition - is a state economic policy as well as economic processes activated or modified by that policy. Any state economic policy manifests itself, above all, in the integration, development and adoption of favourable international co-operation conditions and common economic policy assumptions by the state. Free trade and the development and liberalisation of the flow of capital, means of production, goods and services on an international scale has made possible the extension of available investment area and the geographically diversified (both on a global and regional scale) and functionally integrated operation of globally competing companies. Common and consistent efforts made by highly developed countries to ensure the liberalisation of international trade have resulted in significant elimination of all barriers which may impede that trade. This is being achieved through joint measures taken by those countries within the WTO framework. At the same time, each member of the organisation protects its own domestic market by using increasingly sophisticated trade policy instruments, among which a great role is played by technical standards of products. Due to their number and different origin, books containing technical standards currently in force in Japan cause great problems for foreign exporters. However, a certain hope for changing the existing state of affairs is provided by the signing by Japan of TBT and SPS agreements discussed in the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 47-55